Chicken skin-derived collagen peptides chelated zinc promotes zinc absorption and represses tumor growth and invasion in vivo by suppressing autophagy - Liu, Tengfei; Zou, Lifang; Ji, Xiaowen; Xiao, Guiran (Frontiers in Nutrition, 2022)
To improve the utilization value of chicken by-products, we utilized the method of step-by-step hydrolysis with bromelain and flavourzyme to prepare low molecular weight chicken skin collagen peptides (CCP) (<5 kDa) and characterized the amino acids composition of the CCP. Then, we prepared novel CCP-chelated zinc (CCP–Zn) by chelating the CCP with ZnSO4. We found that the bioavailability of CCP–Zn is higher than ZnSO4. Besides, CCP, ZnSO4, or CCP–Zn effectively repressed the tumor growth, invasion, and migration in a Drosophila malignant tumor model. Moreover, the anti-tumor activity of CCP–Zn is higher than CCP or ZnSO4. Furthermore, the functional mechanism studies indicated that CCP, ZnSO4, or CCP–Zn inhibits tumor progression by reducing the autonomous and non-autonomous autophagy in tumor cells and the microenvironment. Therefore, this research provides in vivo evidence for utilizing chicken skin in the development of zinc supplements and cancer treatment in the future.